Parametric study of leucaena oil bioadhesive formulation: article - Arshad, Nor Atira; Alias, Azil Bahari (2017)
A gradually increase in the value of crude oil and a serious worry about the production of non-renewable energy have encouraged the finding of another renewable sources for fuel, energy and new material production. The aim of this study is to produce and characterize the physical and chemical properties of bio based phenolic resin compound derived from the Leucaena sp. wood by gasification method. This study also carried out to formulate Bio-based phenol formaldehyde adhesive at different condition (temperature, time and catalyst loading) and comparison study with the commercialized petroleum based phenol formaldehyde resole resin adhesive. In order to produce the bio based phenol resin, we use gasification method by using upgraft gasifier reactor while to formulate the phenol formaldehyde which are reaction in the basic condition. The phenol resin and bioadhesive were further analyzed by GC-MS to know the component and composition by percentage in phenolic resin and phenol formaldehyde. The results indicated that the reaction temperature had more effect on the products distribution than the retention time.